DEVELOPMENT AND IMPROVEMENT OF THE QUALITY OF NATURAL FEED BROILER CHICKEN WITH THE ADDITION OF GARLIC LEAVES MEAL TO PRODUCE PRODUCTION PERFORMANCE, CARCASS QUALITY, AND HEALTHY MEAT QUALITY. - Syahrir, Syahrir; Sugiarto, Sugiarto; Marfuah, Nuun; Teguh, Muhammad (AGROLAND The Agricultural Sciences Journal (e-Journal), 2024)
Garlic leaves contain a phytochemical compound, namely allicin which functions as an antimicrobial and antioxidant and can reduce cholesterol and fat in the body so that it can produce healthy chicken growth. Research on meat quality and productivity of broilers obtaining the garlic leaves meal percentage (R0=0; R1=2.5; R2=5.0; R3=7.5; P4=10%) in feed. This study used a completely randomized design (CRD) with The Honest Significant Difference (HSD) as an advanced test. The parameters observed were feed consumption, body weight gain, feed conversion, carcass percentage, and carcass component percentage (chest, upper thigh, lower thigh, back, wings, and abdominal fat). The results showed the addition of garlic leaves meal had a very significant effect (P<0.01) on protein digestibility, energy metabolism, and feed consumption, but had no effect (P>0.05) on body weight gain and feed conversion. Treatment had a significant effect (P<0.05) on the percentage of chicken breast carcass components, a very significant effect (P<0.01) on the upper thigh and lower thigh carcass components but had no effect (P>0.05) on carcass percentage, chicken back and wings. Treatment had a very significant effect (P<0.01) on the percentage of abdominal fat. In conclusion, the treatment gave excellent growth in broilers and produced healthier meat due to the low abdominal fat content.